Cultural Obstacles to the Implementation of Global Accounting Standards in China - Xu, Gina Jin (Auckland University of Technology, 2013)
The purpose of this study is to investigate the cultural and educational issues affecting the implementation of the IFRS-based accounting standards in China. The IASB has a goal to develop a single set of principle-based global accounting standards, which is the IFRS. China has embraced the principle-based regime and its accounting standards have converged substantially with the IFRS. However, research shows that accounting is influenced by the social, cultural and political environment. It is therefore questionable whether the IFRS-based standards can be implemented effectively in a different social and cultural environment. The application of professional judgement is essential in order to operate within a principle-based regime. Therefore, the question is how effectively professional judgement can be exercised in China. Accounting professionals from different backgrounds may reach different judgements, because professional judgement is often influenced by education and cultural values. The current study employed interviews to understand how a Confucian-heritage culture affects the judgement of Chinese accounting professionals within a contemporary backdrop. More specifically, the study analyses how Confucian teachings impact on Chinese accounting education and professional ethics respectively. The interviews were conducted with Chinese accounting professionals, accounting students, accounting academics and foreign practitioners who had worked in China. Their views and experiences on accounting education and the application of professional ethics are sought. Findings reveal that Confucianism is still a substantial influence on Chinese accounting education, which is reflected through a teacher-centred pedagogy and an examination-orientated assessment structure. Under such a system, the critical thinking and analytical skills of accounting students are largely underdeveloped. Hence, students and practitioners are not well prepared for exercising professional judgement. Moreover, Confucian teachings have a strong impact on professional ethics. Professional independence and objectivity are largely compromised under the influences of wulun (the notion of five relationships) and guanxi (interpersonal relationship, networks). Chinese professionals need to follow the obligations and expectations created by Confucian culture, which are not necessarily in line with the concepts of independence and objectivity. Furthermore, Confucian teachings merge with a prevailing materialism that drives accounting professionals to bend the ethical requirements of the profession to survive and/or gain wealth. The findings indicate that Chinese accounting professionals cannot exercise their judgements fairly and effectively within a Chinese cultural environment. This highlights the difficulties of implementing the IFRS principle-based standards in a country that has a different culture from that of Anglo-Saxon countries. Given these cultural obstacles, this study shows that the de facto convergence with IFRS has not been substantial. Both the IASB and Chinese policy makers need to be aware of the cultural obstacles that hinder practitioners from exercising fair judgements. Because Chinese practitioners operate under their own culture, Western ethical concepts may not be applied. Culture is therefore an inherent barrier to developing a set of global standards.
Keywords: IFRS; Confucianism; Guanxi; Accounting education; Professional ethics; China; Professional judgement; Chinese accounting standards